2013
DOI: 10.1007/s12034-013-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanical behaviour of 5% Al2O3-reinforced Fe metal matrix composites (MMCs) produced by powder metallurgy (P/M) route

Abstract: The aim of this paper is to investigate the effect of sintering temperature and time on the properties of Fe-Al 2 O 3 composite (5 wt% Al 2 O 3 ; 95 wt% Fe) prepared by powder metallurgy process. X-ray diffraction, microstructure, density, hardness and compressive strength of prepared samples have been investigated. XRD studies show the presence of Fe and Al 2 O 3 along with iron aluminate phase. Iron aluminate is formed as a result of reactive sintering between iron and alumina particles. Microstructural exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 18 publications
3
52
0
Order By: Relevance
“…The formation of the iron aluminate phase has been reported previously to be generated from Fe-Al 2 O 3 composites under similar ball-milling metallurgy processes from reactive sintering between Fe and Al 2 O 3 . [33,34] Iron aluminate does not have any acidity, which can explain the observed reduced acidity upon Fe incorporation in these materials, and consequently, such a material is not expected to have any catalytic activity in the alkylation reaction. [33,34] To further support this theory, iron aluminate prepared following a literature method [34] was also tested in the alkylation and showed no conversion to products under the investigated conditions.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The formation of the iron aluminate phase has been reported previously to be generated from Fe-Al 2 O 3 composites under similar ball-milling metallurgy processes from reactive sintering between Fe and Al 2 O 3 . [33,34] Iron aluminate does not have any acidity, which can explain the observed reduced acidity upon Fe incorporation in these materials, and consequently, such a material is not expected to have any catalytic activity in the alkylation reaction. [33,34] To further support this theory, iron aluminate prepared following a literature method [34] was also tested in the alkylation and showed no conversion to products under the investigated conditions.…”
mentioning
confidence: 97%
“…[7,20] No lines that correspond to iron oxide nanoparticles could be visualised in this material be- cause of the low Fe loading, but the presence of such Fe 2 O 3 species was confirmed by XPS ( Figure 6). However, most of these reflections were not present in the XRD pattern of Fe 0.5/Z15c-NaOH (green line, Figure 8), which exhibited a broad amorphous band centred at 2 q = 258 and various intense diffraction lines that correspond to the formation of an iron aluminate phase (2 q = 31.8, 37.5-maximum intensity that corresponds to the (3 11) diffraction line-and 44.68), [33,34] with no evidence of the distinctive lines of iron oxide nanoparticles. The formation of the iron aluminate phase has been reported previously to be generated from Fe-Al 2 O 3 composites under similar ball-milling metallurgy processes from reactive sintering between Fe and Al 2 O 3 .…”
mentioning
confidence: 99%
“…But coating with several metals is not possible such as TiAlN. It is also seen that due to thick coatings sometimes edges become round [107][108][109][110][111][112].…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…Formation of nano-iron aluminate and nano-iron zirconium oxide phase improves the hardness, wear, deformation, and corrosion properties of the composites significantly. Formation of these nanophases and their characteristics depend on sintering temperature and time [14][15][16][17][18][19]. Literature studies revealed that there are few reports on using zirconium dioxide (ZrO 2 ) as the reinforcement material in iron matrix [20].…”
Section: Introductionmentioning
confidence: 99%